The Secret Life of Translation Initiation in Prostate Cancer - Hernández, Greco; Ramírez, Jorge L.; Pedroza-Torres, Abraham; Herrera, Luis A.; Jiménez-Ríos, Miguel A. (Frontiers in Genetics, 2019)
Prostate cancer (PCa) is the second most prevalent cancer in men worldwide. Despite the advances understanding the molecular processes driving the onset and progression of this disease, as well as the continued implementation of screening programs, PCa still remains a significant cause of morbidity and mortality, in particular in low-income countries. It is only recently that defects of the translation process, i.e. the synthesis of proteins by the ribosome using a messenger (m)RNA as a template, have begun to gain attention as an important cause of cancer development in different human tissues, including prostate. In particular, the initiation step of translation has been established to play a key role in tumorigenesis. In this review, we discuss the state-of-the-art of three key aspects of protein synthesis in PCa, namely misexpression of translation initiation factors, dysregulation of the major signaling cascades regulating translation, and the therapeutic strategies based on pharmacological compounds targeting translation as a novel alternative to those based on hormones controlling the androgen receptor pathway.